2021
DOI: 10.1002/ange.202109447
|View full text |Cite
|
Sign up to set email alerts
|

Dirhodium‐Catalyzed Enantioselective B−H Bond Insertion of gem‐Diaryl Carbenes: Efficient Access to gem‐Diarylmethine Boranes

Abstract: The scarcity of reliable methods for synthesizing chiral gem-diarylmethine borons limits their applications. Herein, we report am ethod for highly enantioselective dirhodium-catalyzed B À Hbond insertion reactions with diaryl diazomethanes as carbene precursors.These reactions afforded chiral gem-diarylmethine borane compounds in high yield (up to 99 %y ield), high activity (turnover numbers up to 14 300), high enantioselectivity (up to 99 %e e) and showed unprecedented broad functional group tolerance.T he bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…5A and fig. S1, A and B); this value is similar to that for B─H insertion reactions reported in the literature ( 23 27 ). The presence of 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO), a free radical scavenger, in the reaction system had no obvious effect on the product yield, a result that excludes the involvement of a free radical process ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…5A and fig. S1, A and B); this value is similar to that for B─H insertion reactions reported in the literature ( 23 27 ). The presence of 2,2,6,6-tetramethyl-1-piperidinyloxy free radical (TEMPO), a free radical scavenger, in the reaction system had no obvious effect on the product yield, a result that excludes the involvement of a free radical process ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…[15] Although reliable methods for the synthesis of stable and isolable α-boryl carbonyls are rare, the transation-metal catalyzed BÀ H insertion reaction of borane adducts by α-diazo-carbonyl compounds has been reported as the most efficient and straightforward way. [6] In order to test the applicability of [BBN(pz R ) 2 ]Cu(I) complexes IV-VIII in catalysis, we also expand their catalytic activities in BÀ H insertions.…”
Section: Catalytic Carbene Insertion Into Bà H Bondsmentioning
confidence: 99%
“…Transition-meta-catalyzed carbene migratory insertion into CÀ H or XÀ H bonds is a powerful tool for the construction of CÀ C and CÀ X bonds. [1] In the past few years, many types of XÀ H insertions including OÀ H, [2] NÀ H, [3] SÀ H, [4] SiÀ H [5] and recently emerged BÀ H [6] bonds have been realized with different carbene precursors [7] and catalysts. Despite much progress have been made in this type of reaction, in view of its great utility and wide application, the development of new highly efficient and selective catalysts is still in demand.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, the same group developed a Rh-catalysed asymmetric B-H bond insertion reactions of borane adducts and diaryl diazomethanes as a straightforward protocol for various gemdiarylmethine borane compounds in high yield, excellent enantioselectivity, and good functional group tolerance (Scheme 5b). 30 The borane compounds synthesized by this method could be efficiently transformed into synthetically important diaryl methanol, diaryl methyl amine, and triaryl methane derivatives with good stereospecificity. Hammett analysis indicated that the enantioselectivity depended strongly on electronic differences between the two aryl groups of the diazomethane.…”
Section: B-h Bond Insertionmentioning
confidence: 99%